Management of patient adherence to medications: protocol for an online survey of doctors, pharmacists and nurses in Europe. Issue 1 (3rd November 2011) - Clyne, Wendy; Mshelia, Comfort; Hall, Stephanie; McLachlan, Sarah; Jones, Peter; Dobbels, Fabienne; Ruppar, Todd; Siebens, Kaat; Morrison, Val; De Geest, Sabina; Kardas, Premyzlaw
Abstract : Introduction: It is widely recognised that many patients do not take prescribed medicines as advised. Research in this field has commonly focused on the role of the patient in non-adherence; however, healthcare professionals can also have a major influence on patient behaviour in taking medicines. This study examines the perceptions, beliefs and behaviours of healthcare professionals—doctors, pharmacists and nurses—about patient medication adherence. Methods and analysis: This paper describes the study protocol and online questionnaire used in a cross-sectional survey of healthcare professionals in Europe. The participating countries include Austria, Belgium, France, Greece, The Netherlands, Germany, Poland, Portugal, Switzerland, Hungary, Italy and England. The study population comprises primary care and community-based doctors, pharmacists and nurses involved in the care of adult patients taking prescribed medicines for chronic and acute illnesses. Discussion: Knowledge of the nature, extent and variability of the practices of healthcare professionals to support medication adherence could inform future service design, healthcare professional education, policy and research.